Hellenica World

.

Abel's binomial theorem, named after Niels Henrik Abel, states the following:

\( \sum_{k=0}^m \binom{m}{k} (w+m-k)^{m-k-1}(z+k)^k=w^{-1}(z+w+m)^m. \)

Example
m = 2

\( \begin{align} & {} \quad \binom{2}{0}(w+2)^1(z+0)^0+\binom{2}{1}(w+1)^0(z+1)^1+\binom{2}{2}(w+0)^{-1}(z+2)^2 \\ & = (w+2)+2(z+1)+\frac{(z+2)^2}{w} \\ & = \frac{(z+w+2)^2}{w}. \end{align} \)

See also

Binomial theorem
Binomial type

References

Weisstein, Eric W., "Abel's binomial theorem" from MathWorld.

Mathematics Encyclopedia

Retrieved from "http://en.wikipedia.org/"
All text is available under the terms of the GNU Free Documentation License

Home